In vivo Study of Sealing Capability of Raw Propolis Extract and Calcium Hydroxide on Dentin Surface - Roelianto M; Wahjuningrum DA; Pamungkas YB; Zubaidah N; Permatasari RI; Dianti E (Dove Medical Press, 2020)
Muhamad Roelianto, Dian Agustin Wahjuningrum, Yusuf Bagus Pamungkas, Nanik Zubaidah, Ryza Indah Permatasari, Eska Dianti Department of Conservative Dentistry, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Jawa Timur 60132, IndonesiaCorrespondence: Dian Agustin WahjuningrumDepartment of Conservative Dentistry, Faculty of Dental Medicine, Universitas Airlangga, Mayjen Prof. Dr. Moestopo 47, Surabaya, Jawa Timur 60132, IndonesiaTel +62 315030252Fax +62 315022472Email dian-agustin-w@fkg.unair.ac.idAim: This research aimed to investigate the differences in the sealing capability of propolis extracts and Ca(OH)2 on dentin surfaces.Materials and Methods: Eighteen mandible incisors of Wistar rats were prepared at a depth of 0.5 mm after which they were randomly divided into 3 groups (n=6) including control (C), pulp-capped with Ca(OH)2 group (P1), and indirect pulp-capped with propolis extract group (P2). All the cavities were sealed with glass ionomer restorative cement. Moreover, the sections of the teeth were obtained after six Wistar Rats from each group were sacrificed on the second day after treatment. The rats’ incisors were cleaved transversally to the area where Ca(OH)2 and propolis extract bonded with dentin for the SEM (scanning electron microscope) analysis and examined using microphotographs test with 5000x magnification. All the samples were measured and examined with spectrophotometry test to determine the bonding distance between Ca(OH)2 and dentin, as well as propolis extract and dentin. The result from the two tests was analyzed with SPSS using an independent t-test at p < 0.05.Results: There were significant differences between the calcium hydroxide and propolis extract groups (p< 0.05) based on the results obtained in the form of spectrums chemical functional groups of spectrophotometry examination. No new chemical bonding or compound was also observed to have been formed between propolis extract with dentin as well as calcium hydroxide with dentin.Conclusion: The adaptation or sealing capability of propolis extract was found to be better than calcium hydroxide to the dentin surface.Keywords: pulp capping, sealing ability, calcium hydroxide, propolis, scanning electron microscope, spectrophotometry